Avaliação da influência do sistema de polimento na topografia superficial de diferentes resinas compostas - Correia, Ayla Macyelle de Oliveira (2016)
Several polishing protocols have been assessed for their effect on the surface roughness of restorative materials. However, the effect of polishing systems on surface roughness depend on the composite used. The aim of this study was to evaluate the influence of two different polishing systems (Diamond Pro, FGM - DP; Jiffy® Polishers, Ultradent Products - JP) combined to three composites: nanoparticle (Filtek ™ Z350 XT, 3M / ESPE), nanohybrid (IPS Empress Direct, Ivoclar Vivadent Ltd.) and microhybrid (Vit-l-escence®, Ultradent Products). Fifty-four pecimenss were prepared in a metallic matrix (10 mm x 2 mm) and polymerized under a polyester strip. The specimens were identified and randomly distributed into six groups (n = 9) in accordance to the polishing system. Surface roughness was measured at baseline E0 (polyester strip), E1 (diamond burs), E2D (Diamond Pro) and E2J (Jiffy® polishers) by a profilometer. Data were collected and analyzed. To qualitatively analyze the surface, one specimen from each group was analyzed by atomic force microscopy (AFM). According to the Paired t-test (p <0.05), there was no significant difference between the roughness values obtained in E0 and E2D for nanoparticle composites (p = 0.463) and nanohybrid (p = 0.423). However, for microhybrid composite, using both polishing systems led to significantly rougher surfaces than E0. The AFM showed that surface roughness is related to particle morphology. It was concluded that the surface roughness is dependent on composite and polishing system.